Modified the CG-Algorithm for Unconstrained Non-Linear Optimization by Using Oren’s Update - Abbas Al-Bayati (Al-Rafidain Journal of Computer Sciences and Mathematics, 2005)
In this paper we have modified a new extended generalized conjugate gradient steps with self-scaling variable metric updates for unconstrained optimization. The new proposed algorithm is based on the inexact line searches and it is examined by using different non-linear test functions with various dimensions.